2017
DOI: 10.1111/2041-210x.12921
|View full text |Cite
|
Sign up to set email alerts
|

An efficient method to exploit LiDAR data in animal ecology

Abstract: Light detection and ranging (LiDAR) technology provides ecologists with high‐resolution data on three‐dimensional vegetation structure. Large LiDAR datasets challenge predictive ecologists, who commonly simplify point clouds into structural attributes (namely LiDAR‐based metrics such as canopy height), which are used as predictors in ecological models, potentially with loss of relevant information. We illustrate an efficient alternative approach to reduce the dimensionality of LiDAR data that aims at minimal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…However, choosing the right metrics is not always easy and might depend on a priori ecological knowledge of animal habitat use. In cases where such knowledge is lacking, it is also possible to condense the variability in LiDAR point clouds by generating principal components as predictors and using them in exploratory analyses with animal species distribution data to generate hypotheses about animal habitat and space use (Ciuti et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, choosing the right metrics is not always easy and might depend on a priori ecological knowledge of animal habitat use. In cases where such knowledge is lacking, it is also possible to condense the variability in LiDAR point clouds by generating principal components as predictors and using them in exploratory analyses with animal species distribution data to generate hypotheses about animal habitat and space use (Ciuti et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…LiDAR‐derived vegetation metrics (e.g., mean canopy height) are then calculated to summarize the vegetation structural information from the point cloud within each pixel or voxel. An advantage of such area‐based approaches (i.e., rasterization) and voxel‐based approaches (i.e., voxelization) is that they are computationally efficient, but they also lead to information loss regarding the 3‐D information of the point cloud (Ciuti et al, ). An alternative is to use object‐based approaches (Figure b) where either the point cloud or a derived rasterized map is segmented into objects such as trees, forest stands, reed beds or hedges based on similarities and differences in neighbourhood information around points or grid cells (Höfle, Hollaus, & Hagenauer, ; Koch, Kattenborn, Straub, & Vauhkonen, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the case this resulted in eleven principal components (PC), which were used as new predictor variables in the final statistical analyzes. With this setup, we followed the procedure described in Ciuti et al [21]. To account for possible nonlinear relationships between the predictors and the response we used generalized additive models (GAMs).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The remote sensing (RS) discipline mainly describes forest structure by summarizing variables that can 2 of 20 be determined from sensor data. These include maximum height, quantiles of height from surface models or point clouds, point densities, or structural complexity indices, tree counts, biomass estimates and many more [3,[13][14][15][16][17][18][19][20][21][22][23][24][25][26]. If the aim is to provide a broader perspective of the forest structure, metrics such as the Stand Structural Complexity Index (SSCI) [4] are for instance applicable.…”
Section: Introductionmentioning
confidence: 99%
“…A sensitivity analysis showed that at least seven random points associated to each orangutan relocation were needed to obtain stable model estimates. Therefore, we opted to draw ten random points per used location to obtain robust parameter estimates [67] (Table 1).…”
Section: Methodsmentioning
confidence: 99%